2020
DOI: 10.1016/j.envdev.2020.100497
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Pattern of Land Degradation from 1990 to 2015 in Mongolia

Abstract: Highlights  A map of land degradation and restoration with 30 m resolution in Mongolia was obtained for the first time.  For the past 25 years, the trend of land change in Mongolia was dominated by land degradation.  Land degradation is accompanied by ongoing restoration of some land areas, and the capacity for land restoration is gradually improving.  The central regions of Mongolia are the area with the most significant land degradation, and the combined effects from natural and socioeconomic factors are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 13 publications
(11 reference statements)
1
25
0
Order By: Relevance
“…This finding is also consistent with that of a previous study, which showed that overall trends of average annual temperature and precipitation have been increasing worldwide from 2000 to 2014 [81]. In addition, the ESA land cover map showed barren land has decreased over the study period, also supported by [82], and the vegetated area has increased. This land-use change could be a reason that annual NPP has risen slightly in the study area.…”
Section: Inter-annual Variations In Nppsupporting
confidence: 92%
“…This finding is also consistent with that of a previous study, which showed that overall trends of average annual temperature and precipitation have been increasing worldwide from 2000 to 2014 [81]. In addition, the ESA land cover map showed barren land has decreased over the study period, also supported by [82], and the vegetated area has increased. This land-use change could be a reason that annual NPP has risen slightly in the study area.…”
Section: Inter-annual Variations In Nppsupporting
confidence: 92%
“…Inner Mongolia is located in arid and semi-arid regions, which are the most severely desertified regions in China. According to statistics, land desertification in Inner Mongolia has developed rapidly since the 1990s, with > 76% of the land in Inner Mongolia suffering from desertification to varying degrees by 2017 [72,96]. To better prevent and control land desertification, scholars have proposed a series of prevention and control measures.…”
Section: Suggestions For Vegetation Restorationmentioning
confidence: 99%
“…Due to tremendous economic growth and rapidly expanding urban development, as well as over cultivation and grazing behaviors, China has undergone great land degradation over the past few decades [13,14]. Since the 1970's, large-scale ecological projects have been launched in China by the central government with the aim of preventing water loss and soil erosion and ensuring sustainable development (e.g., the Three-North Forest Shelterbelts Program launched in 1979 and the Grain for Green Program implemented in 1999) [15][16][17].…”
Section: Study Areamentioning
confidence: 99%